Part of the Book of common prayer, and administration of the sacraments, and other rites and ceremonies of the Church, according to the use of the Church of England [electronic resource] - Church of England.; Kirkby, W. W. (William West), 1827-1907.; Bompas, William Carpenter, 1834-1906. (London : Society for Promoting Christian Knowledge, 1891)
Mostly in Chipewyan, roman characters, with headings and instructions in English. Electronic reproduction. Mode of access: Internet. 44